Pemeriksaan Payudara Klinis pada Wanita Usia Subur di Puskesmas Bakunase dengan Pendekatan Health Belief Model - Bernadetha P. Ewang; Helga J. N Ndun; Eryc Z. Haba Bunga (Yayasan Literasi Sains Indonesia, 2025)
Women of Childbearing Age (WCA) are at risk of breast cancer. Clinical Breast Exam (CBE) performed by healthcare professionals can help detect breast cancer early. However, the national coverage of CBE of 80% has not been met because the target achieved is only 13.7%. The coverage of CBE at the Bakunase Health Center has not met the target because it only reached 8.95% in 2023. This study aims to explore the experience of WCA in conducting CBE using the Health Belief Model approach. The research was descriptive with a qualitative approach. The informants consisted of eight women selected by using a purposive sampling technique. The results of the study found that informants felt susceptible to breast cancer if they had risk factors. The perceived severity of breast cancer was related to mastectomy and the risk of death. Breast cancer was considered curable with medical and herbal treatments. CBE was considered beneficial for informants because it could help detect symptoms of breast cancer early. Informants generally felt they had no obstacles to performing CBE, but some informants found it difficult to divide their time and felt afraid when deciding to perform CBE. The cues to act were encouragement from oneself (internal) and mass media, namely the internet, and advice from parents, husbands, and health workers (external). Self-efficacy in performing CBE was based on the informant's knowledge and experience. Education about breast cancer and CBE needs to be carried out regularly to increase knowledge that will encourage WRA to perform CBE.